A Mixed Method Study on Kidney Transplant Recipients’ Quality of Life - Bheru Singh Chundawat; Dharmesh Chaturvedi; Vaneshvar Suthar; Kapil Gupta; Kaushlendra Singh Yadav; Shweta Pattnaik (Indian Journal of Transplantation)
Background: Chronic kidney disease is progressive irreversible deterioration in renal function where body is unable to maintain metabolic, fluid, and electrolyte balance. It occurs with a gradual reduction in the function of the kidneys over time. The purpose of the study was to gain deeper understanding of the quality of life (QoL) of kidney transplant recipients. Materials and Methods: A sequential exploratory research design was adopted in the study. The study was conducted in the nephrology outpatient department unit of Choithram Hospital and Research Centre, Indore. Nonprobability purposive sampling technique was used to collect data from the participants. The data were then analyzed using descriptive and inferential statistics. Results: During the data analysis in qualitative research design, five themes emerged, which were Physical life, Social life, Economic improvement, Change in attitude toward life, and Challenges. Sixty percent of kidney transplant recipients had a good QoL. The quantitative study results supported the themes that emerged from the qualitative study. Conclusion: The Study concluded that transplant certainly improves the QoL so there should be counseling for patients regarding kidney transplantation. It was very imperative from the viewpoint of the medical professionals to support renal transplant but in our research findings, kidney transplant recipients were also in favor of kidney transplant.